Formulation and validation of an Enabling Developmental Environment Scale (EDES) for local economic development (LED - Meyer, Daniel Francois; Keyser, ElsabÃ (Journal of Economics and Behavioral Studies, 2018)
Local government is one of the main role players in local economic development (LED) and need to assist in the creation of an enabling developmental environment for local businesses to prosper. Partnerships are required between local government, businesses and communities for regions to develop, yet in many cases government at this level fails to create this developmental enabling environment. This research has as its focus on the formulation and validation of an Enabling Developmental Environment Scale (EDES). This scale will allow local government to be evaluated, assessed and compared regarding the creation of such a developmental environment. The pilot study involved152 participants from the Vaal Triangle region, South Africa. Reliability and construct validity of the instrument weretested by using the Cronbach’s Alpha Coefficient and Varimax Factor Analysis. It is evident from the results that thescale is a valid and reliable tool for researchers to evaluate and assess the level of an enabling environment as created by local government in a specific region.